Pengaruh Good Public Governance Terhadap Pengelolaan PNPB dari Pemanfaatan Barang Milik Negara - Sari Tirto Warino; Endang Etty Merawati; Widarto Rachbini (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2026)
Main Purpose – This study aims to analyze the effect of transparency, accountability, and competence on the optimization of non-tax state revenue management from the utilization of state-owned assets, with competence as a moderating variable. Method – A quantitative approach using purposive sampling techniques on PNBP/BMN management employees was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Main Findings – Transparency and accountability do not have a significant effect on the optimization of PNBP management from the utilization of BMN, while competence has a positive and significant effect. In addition, competence does not moderate the relationship between transparency and accountability on the optimization of PNBP management.. Theory and Practical Implications – The results of the study reinforce the concept of Good Public Governance, which places competence as the main driving factor for the effectiveness of state asset management. These results highlight the need for continuous development of employee competence. Novelty - The novelty of this study lies in the integration of competency variables as moderators in the relationship between transparency and accountability towards the optimization of PNBP management from the utilization of BMN within central government agencies.